ANALISIS PERAN GURU PADA PROSES PEMBELAJARAN - Darmawan Harefa; Hemat Zagoto (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
The research aims to describe the teacher's role in the learning process. The research method uses descriptive research using a qualitative approach. Data collection techniques are observation, interviews, documentation and triangulation/combination. The researcher made observations in the field by noting the role of the teacher in the learning process in class VIII SMP Negeri 3 Toma. The findings of the research are the teacher's lack of attention in the child's learning process, the teacher's lack of understanding to children that by learning children's aspirations will be achieved, the way parents give gifts and punishments in the learning process is not optimal, the learning facilities provided by parents for children are lacking, the teacher's response when the child has less learning difficulties. Based on the results of this study, it can be concluded that the role of the teacher, especially at SMP Negeri 3 Toma, is very sufficient to provide encouragement to students so that students remain enthusiastic in learning. Suggestions, teachers are expected to be able to understand their role in dealing with various conditions so that students are always motivated and have enthusiasm in learning.